How do text type, prior vocabulary knowledge, and working memory capacity affect second language incidental vocabulary learning through reading? - Lim , Soomin; Lee, Sang-Ki (Studies in Second Language Learning and Teaching, 2025)
Incidental vocabulary learning through reading may be influenced by a range of learner-internal as well as learner-external factors. This study, specifically, examined the potential impacts of three factors: text type, prior L2 vocabulary knowledge, and working memory capacity. Forty-six 1st grade high school students in Korea completed a battery of tests: (a) the Vocabulary Levels Test and (b) a reading span task as measures of prior vocabulary knowledge and working memory capacity, respectively. All the participants read two texts (one narrative and one expository) containing pseudowords and completed two reading comprehension tasks. Immediately after reading and again two days later, two measures of vocabulary gains were administered: (a) a form recognition test and (b) a meaning recognition test. The results revealed that the narrative text was more effective in aiding L2 vocabulary acquisition in the long term than the expository text. Both prior vocabulary knowledge and working memory capacity played facilitative roles in the lexical inferencing process and retention, but working memory capacity had much stronger effects throughout all the posttests. A significant interaction between text type and working memory capacity was also observed, suggesting that the text type effective for incidental learning differed according to learners’ individual differences in language learning aptitude. Some implications for designing the classes that implement incidental vocabulary learning are discussed.